Training to Analyze Functional Parameters with Fiberoptic Endoscopic Evaluation of Swallowing: A Scoping Review - Costa, Bianca O. I.; Machado, Liliane S.; Augusto, Milena M.; Magalhães, Desiré D. D.; Alves, Thaís Coelho [UNESP]; Pernambuco, Leandro (Springer Nature, 2024)
Analyzing fiberoptic endoscopic evaluation of swallowing (FEES) is challenging and requires training to ensure the proficiency of health professionals and improve reliability. This scoping review aims to identify and map the available evidence on training health professionals to analyze FEES functional parameters. The method proposed by the Joanna Briggs Institute and the PRISMA-ScR guidelines were followed. The search was performed in MEDLINE, Cochrane Library, Embase, Web of Science, Scopus, CINAHL databases, and in the gray literature. Two blinded independent reviewers screened articles by title and abstract. Then, they read the full text of the included reports, considering the eligibility criteria. Data were extracted using a standardized form. Six studies met the established eligibility criteria, published between 2009 and 2022, with few participants. All these studies addressed training as part of the process to validate a rating scale. No standardized criteria were observed regarding the selection of experts and participants, training structure, and outcome measures to assess participants’ competence. The reviewed literature indicates that training must be developed to equip students and health professionals who treat dysphagia, enabling them to analyze the functional parameters of the FEES, considering variables that may influence the participants’ performance.
Keywords: Deglutition disorders; Education; Endoscopy; Swallowing; Training